MINERAL SURFACE CATALYSIS OF REACTIONS BETWEEN FEII AND OXIME CARBAMATE PESTICIDES - Strathmann T.J.; Stone A.T. (My University, 2003)
This study examines the reduction of oxime carbamate pesticides (oxamyl, methomyl, and aldicarb) by FeII in aqueous suspensions containing twelve different (hydr)oxide and aluminosilicate minerals. In the absence of FeII, mineral surfaces have no apparent effect on the pathways or rates of oxime carbamate degradation. In anoxic suspensions containing FeII and mineral surfaces, rates of oxime carbamate reduction are significantly faster than in equivalent mineral-free homogeneous solutions. Rates increase with increasing surface area loading (mineral surface area per volume of suspension) and pH. Kinetic trends are interpreted in terms of changes in FeII speciation. Quantitative modeling indicates a first-order dependence on total adsorbed FeII concentration and no significant dependence on adsorbed oxime carbamate concentration. Bimolecular rate constants describing the reactivity of adsorbed FeII with dissolved oxamyl decrease in the following order: silicon dioxide #2 > silicon dioxide #1 # hematite #2 > titanium dioxide #1 > hematite #1 > titanium dioxide #2 > silicon dioxide #3 > aluminum oxide > kaolinite #1 > kaolinite #2 > goethite # titanium dioxide #3. Possible factors responsible for the increased reactivity of adsorbed FeII, as well as for the relative reactivity of FeII adsorbed on different surfaces, are discussed. Results from this study demonstrate that mineral surfaces present in subsurface environments can substantially catalyze the reduction of oxime carbamate pesticides by FeII. Overall rates of pesticide degradation may be under predicted by > 1 order of magnitude if the effects of mineral surfaces are not accounted for.